Preparation of high-purity tantalum ethoxide by vacuum distillation - 杨声海 陈永明 杨海平 刘银元 唐谟堂 邱冠周 (Transactions of Nonferrous Metals Society of China, 2008)
Effects of reflux ratio, water addition and content of water in ethanol on the purity and yield of tantalum ethoxide during vacuum distillation were investigated under the operational conditions of pressure of 1kPa, oil bath temperature of 210-230 ℃, and outlet temperature of 190℃. The condensate sample was characterized by FTIR, 1↑H-NMR spectroscopy and Raman spectra, respectively. The contents of tantalum, carbon and hydrogen in the sample were also determined with elemental analysis instrument. The obtained results consistently demonstrate that the condensate is tantalum ethoxide. The content of impurity, such as Al, As, Ca, Co, Cr, Cu, Fe, K, Mg, Mn, Mo, Na, Ni, Pb, Sn, Ti, V and Zn, in tantalum ethoxide is less than 0.000 05%, while Nb content is less than 0.000 5%. The content of impurities in tantalum ethoxide sample excels that of Epichem Group＇s requirement for Ta（OC2H5）5 of 99.999%.